2010
DOI: 10.1002/adma.200902985
|View full text |Cite
|
Sign up to set email alerts
|

Bulk Photovoltaic Effect at Visible Wavelength in Epitaxial Ferroelectric BiFeO3 Thin Films

Abstract: Appreciable photovoltaic responses to visible light are observed in epitaxial ferroelectric BiFeO3 thin films by sputtering deposition. The photocurrent direction is opposite to the BiFeO3 polarization vector and can be switched by poling the films in different directions (see figure). The as‐deposited films are strongly self‐polarized, exhibiting significant photovoltaic response before any electrical poling process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
465
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 564 publications
(486 citation statements)
references
References 32 publications
16
465
5
Order By: Relevance
“…Second, as shown in the upper left insets of Figures 1c and d, these features commonly exhibit a photovoltaic effect in the low-E-field region, consistent with the literature. [3][4][5][6][7][8] Figures 2a and d show the in-plane domain images and the corresponding I sc images for single-domain switching. In the intermediate reversal field, as in the domain image of E poling at þ 45 V and the I sc image at À20 V, the domain breaks up into two subdomains, showing signs of I sc to each other.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, as shown in the upper left insets of Figures 1c and d, these features commonly exhibit a photovoltaic effect in the low-E-field region, consistent with the literature. [3][4][5][6][7][8] Figures 2a and d show the in-plane domain images and the corresponding I sc images for single-domain switching. In the intermediate reversal field, as in the domain image of E poling at þ 45 V and the I sc image at À20 V, the domain breaks up into two subdomains, showing signs of I sc to each other.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon has been recently revisited with a small band-gap, BiFeO 3 (BFO) ferroelectric, from which a substantially higher photon-to-charge generation efficiency can be achieved in the visible range compared with that of other insulating ferroelectrics. [3][4][5][6][7][8] reported that diodelike rectification follows the polarization-dependent interface bandbending of BFO single-crystal slabs that are electrically switchable, that is, V oc and I sc are defined by the remanent polarization directions. In general, the spatial extent of spontaneous polarization vectors in ferroelectric crystals is typically manifested as domains (typically spanning over a few mm in size) and domain walls (DW, 1-2 nm in…”
mentioning
confidence: 99%
“…Bulk polarization is not required; only inversion symmetry must be broken. Shift currents have been investigated experimentally [19,[27][28][29][30][31][32][33][34], analytically [20,23,[35][36][37], and computationally, although only for a few nonpolar materials [23][24][25]. Perturbative analysis treating the electromagnetic field classically yields the shift current expression [20,23] J q ¼ rsq E r E s rsq ð!Þ ¼ e e m@!…”
Section: First Principles Calculation Of the Shift Current Photovoltamentioning
confidence: 99%
“…Shift current materials have been suggested as candidates for light-harvesting energy applications, due to active photocurrent generation in the entire bulk of the material and their above-band gap photovoltages [47]. The BPVE is a ballistic hot carrier effect.…”
mentioning
confidence: 99%